2005
DOI: 10.1007/s00170-003-2010-6
|View full text |Cite
|
Sign up to set email alerts
|

A synthetic control chart for monitoring process dispersion with sample range

Abstract: A synthetic control chart for monitoring the changes in the standard deviation of a normally distributed process is proposed in this paper. The synthetic chart consists of the sample range (R) chart and the conforming run-length (CRL) chart. The R chart can be viewed as a special case of the synthetic chart. The operation, design and performance of this chart are described. Average run-length comparisons between other procedures and the synthetic chart are presented. It indicates that the synthetic chart is a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
32
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 24 publications
0
32
0
Order By: Relevance
“…So, the study of a chart which can detect both upward and downward shifts in the process dispersion becomes necessary and important. Along with these ideas, we extend the one-sided synthetic charts introduced by Chen and Huang (2005) and Huang and Chen (2005) and propose a two-sided synthetic S 2 chart to monitor the process dispersion.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…So, the study of a chart which can detect both upward and downward shifts in the process dispersion becomes necessary and important. Along with these ideas, we extend the one-sided synthetic charts introduced by Chen and Huang (2005) and Huang and Chen (2005) and propose a two-sided synthetic S 2 chart to monitor the process dispersion.…”
Section: Introductionmentioning
confidence: 98%
“…Chen and Huang (2005) and Huang and Chen (2005) developed the synthetic charts for monitoring the process dispersion with the sample standard deviations and sample ranges, respectively. Khilare and Shirke (2012) proposed the nonparametric synthetic chart which is a combination of the sign sub-chart and the CRL sub-chart for detecting the increases in the process variation.…”
Section: Introductionmentioning
confidence: 99%
“…For the univariate case, many innovations have been proposed to improve the charts' performance, such as the CUSUM charts (see Page 1 and Reynolds and Stoumbos 2 ), the EWMA charts (see Lucas and Saccucci 3 and Costa and Rahim 4 ), the adaptive charts (see Costa 5,6 and De Magalhães et al 7 ), the double sampling charts (see Daudin 8 ) and the synthetic charts (see Wu and Spedding 9,10 , Wu et al 11 , Wu and Yeo 12 , Calzada and Scariano 13 , Davis and Woodall 14 , Scariano and Calzada 15 , Gadre and Rattihalli 16 , Chen and Huang 17 and Huang and Chen 18 ).…”
Section: Introductionmentioning
confidence: 98%
“…It was shown that the synthetic X chart outperforms the Shewhart X chart over the entire range of shifts in the process mean. The development of the synthetic control chart for a univariate process has been also documented by Calzadaand Scariano [4], Davis and Woodall [5], Scariano and Calzada [6], Huang and Chen [7], and Costa and Rahim [8]. The development of the Multivariate synthetic control chart for monitoring process Mean vector (MV-Syn-M) has been proposed by Ghute and Shirke [9].…”
Section: Introductionmentioning
confidence: 99%